Power, Poverty and Prayer: A Historical Perspective on the Church in the African Sate at the Edge of the Twenty-First Century - Kalu, Ogbu U. (Toronto journal of theology, 1999)
In the early 1990s Adrian Hastings, a consummate historian, theologian and social activist intoned that "Black Africa is today totally inconceivable apart from the presence of Christianity, a presence which a couple of generations ago could still be reasonably dismissed as fundamentally marginal and a mere subsidiary aspect of colonialism." An African theologian Kwame Bediako cast his mind back to the Edinburgh Conference of 1910 and traced the contours of this element of surprise in the transformation of African Christianity. He declared that African Christianity has now acquired a greater consciousness of its African identity and character. The great challenge for the future is how to be of service to Africa as it voyages into the political realm of the twenty-first century. Not only have "new dimensions" emerged in African Christian spirituality as Paul Gifford said, but the roles of Christian leaders in the contemporary political crises have grown tremendously. Bediako and Gifford cite Togo, Benin, Ghana, and Liberia in West Africa, Zaire, Malawi and Zambia in Central Africa and South Africa as examples.